Computerisation of POPSl - Ravichandra Rao, I. K. (Journal of Information and Knowledge, 1976)
Computer program for generation of alphabetical subject index-Postulate-based Permuted Subject Indexing ( =POPSI) is described. Two rules for choice of Lead Term for facets in case of Parts of Core Entity of Study are given.